An evaluation of government low cost housing layout plans and facilities in Kuala Lumpur - Zulkifli , Nurul Hidayah; Abdullah, Fadzidah; Sapian, Abdul Razak (2012)

(untitled)
In Malaysia, low cost housing development is undertaken by both the public and private sectors. Since 1984, Kuala Lumpur Plan (KLSP) has been trying to ensure that sufficient houses would be provided for all income groups in Kuala Lumpur . Thus, Kuala Lumpur’s residents could be properly served in terms of infrastructure, utilities and community facilities. Based on the Ninth Malaysia Plan, space standard for low cost housing for new projects has been revised from minimum of 650 square foot, to 700 square foot per unit. The same space standard also applies to housing units allocated for people with disabilities (PwD) . The objective of this research is to identify the minimum comfort size of house of PPR (Program Perumahan Rakyat), both for the general public’s unit and PWD’s unit. In addition, this research also intends to determine the suitable ratio for car parking in government low cost high-rise housing. Besides, this research will propose recommendation to improve housing size and car parking provision. These findings can help government and related agencies to better understand the current issues in low-cost housing, based on people’s perspectives. It is hoped that the findings of this research may help government agencies to improve the implementation and provision of low-cost housing development in Malaysia.